2012
DOI: 10.1182/blood-2012-02-387092
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the challenge of hematologic malignancies in sub-Saharan Africa

Abstract: Cancer is a leading cause of death and disability in sub-Saharan Africa and will eclipse infectious diseases within the next several decades if current trends continue. Hematologic malignancies, including non-Hodgkin lymphoma, leukemia, Hodgkin lymphoma, and multiple myeloma, account for nearly 10% of the overall cancer burden in the region, and the incidence of non-Hodgkin lymphoma and Hodgkin lymphoma is rapidly increasing as a result of HIV. Despite an increasing burden, mechanisms for diagnosing, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 81 publications
6
97
5
1
Order By: Relevance
“…22.2% of the patients in current study presented with elevated T3, T4 hormones, but studies by Felemban et al, showed only 3.3% cases, and study done in USA reported 10% cases. The reason is unknown.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…22.2% of the patients in current study presented with elevated T3, T4 hormones, but studies by Felemban et al, showed only 3.3% cases, and study done in USA reported 10% cases. The reason is unknown.…”
Section: Discussioncontrasting
confidence: 39%
“…Hence there were no complications reported in our study. Although preliminary results are promising, a great limitation to the study is incomplete information, commonly encountered in clinical care and program evaluation in similar settings 20,21,22 . Both incomplete information and incomplete documentation affect appropriate risk stratification, a challenge in GTN management that has been noted in cancer centers in lowresource settings 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However these figures are based on sparse adult cancer registries. HL is most likely to develop during the first months of antiretroviral therapy and with moderate CD4 lymphopenia (Gopal et al, 2012).…”
Section: Hiv and Hlmentioning
confidence: 99%
“…Development of evidence-based guidelines oriented specifically for LMICs will be an important step towards improving the health care systems in these countries. Even though these 'local' guidelines may recommend use of strategies different from those used in HICs, they will be aimed at achieving the best standard of care that is practicable in LMICs (Anderson et al, 2006;Gopal et al, 2012).…”
Section: Applicability Of Guidelines To Lmicsmentioning
confidence: 99%